Does the Stock Market Overreact?: Discussion - Bernstein, Peter L. (Journal of Finance, 1985)
Peter L. Bernstein, Does the Stock Market Overreact?: Discussion, The Journal of Finance, Vol. 40, No. 3, Papers and Proceedings of the Forty-Third Annual Meeting American Finance Association, Dallas, Texas, December 28-30, 1984 (Jul., 1985), pp. 806-808